,Fit machen' für die Ausbildung Eine Ethnografie zu Unterricht in der Berufsvorbereitung - Thielen, Marc (Verlag Barbara Budrich, 2021)
In light of the high importance of soft skills in the context of dual vocational training in Germany, the behaviour of young people is currently the focus of pedagogical institutions at the transition from school to work. Societal ideas about the behaviours considered necessary for successful training are realised in vocational preparation programmes of the transition sector in a specific pedagogical order, which this study ethnographically illuminates.